Tingkat Pengetahuan Swamedikasi Gastritis pada Siswa Sekolah Menengah Atas Di Tembilahan Propinsi Riau - Devia, Uci Asna; Oktianti, Dian (Indonesian Journal of Pharmacy and Natural Product, 2022)
Self-education is part of the community's efforts to maintain its own health. Gastritis is an inflammation or bleeding in the gastric mucosa caused by irritants, infections, and irregularities in diet, such as late eating, eating too much, eating fast, eating too many spicy spices, consuming high protein and drinking excessive coffee. The purpose of this study is to find out the level of knowledge of students on gastritis self-research. This research uses quantitative descriptive research methods. Data retrieval technique uses consecutive sampling technique with the number of 98 respondents, with research instruments that are google form kuisioner. Data analysis uses descriptive analysis. The number of respondents based on schools, namely Pharmacy Vocational School with 58 respondents and SMK N 2 Tembilahan with 40 respondents. The results showed that the percentage of questions that answered the questions correctly were 69% of Pharmacy Vocational School students and 60% of SMAKN 2 students. The level of knowledge of vocational school students about gastritis self-research belongs to the good category of 36 respondents (62%), and quite as many as 22 respondents (38%). While the level of knowledge of SMKN 2 Tembilahan students about gastritis self-sufficiency belongs to the good category of 15 respondents 37%), enough as many as 9 respondents (23%), and less as many as 16 respondents (40%). ABSTRAKSwamedikasi merupakan bagian dari upaya masyarakat untuk menjaga kesehatannya sendiri. Gastritis merupakan suatu peradangan atau perdarahan pada mukosa lambung yang disebabkan oleh faktor iritasi, infeksi, dan ketidak teraturan dalam pola makan, misalnya telat makan, makan terlalu banyak, makan cepat, makan-makanan yang terlalu banyak bumbu pedas, mengonsumsi protein tinggi dan minum kopi berlebihan. Tujuan penelitian ini adalah untuk mengevaluasi tingkat pengetahuan pelajar terhadap swamedikasi gastritis. penelitian ini menggunakan metode penelitian deskriptif kuantitatif. Teknik pengambilan data menggunakan teknik consecutive sampling dengan jumlah 98 reponden, dengan instrumen penelitian yaitu kuisioner google form. Analisa data menggunakan analisa deskriptif. Jumlah Responden berdasarkan sekolah yaitu SMK Farmasi dengan 58 responden dan SMK N 2 Tembilahan dengan 40 responden. Hasil penelitian menunjukan bahwa pertanyaan ersentase yang menjawab pertanyaan dengan benar siswa SMK Farmasi sebanyak 69% dan SMAKN 2 ada 60%. tingkat pengetahuan pelajar SMK Farmasi tentang swamedikasi gastritis termasuk kategori baik sebanyak 36 responden (62%), dan cukup sebanyak 22 responden (38%). Sedangkan tingkat pengetahuan pelajar SMKN 2 Tembilahan tentang swamedikasi gastritis termasuk kategori baik sebanyak 15 responden (37%), Cukup sebanyak 9 responden (23%), dan kurang sebanyak 16 responden (40%).Â